2016
DOI: 10.1186/s12899-016-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of angiotensin II in the newborn period: role of type 1 and type 2 receptors

Abstract: BackgroundEvidence suggests a critical role for the renin-angiotensin system in regulating renal function during postnatal development. However, the physiological relevance of a highly elevated renin-angiotensin system early in life is not well understood, nor which angiotensin receptors might be involved. This study was designed to investigate the roles of angiotensin receptors type 1 (AT1R) and type 2 (AT2R) in regulating glomerular and tubular function during postnatal development.MethodsThe renal effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…However, our data at least indicated that ANG II‐AT 1 R axis played important roles in EAM development and CD11b + Ly6C + cells reprogramming. And our data also were in line with published reports that most actions of ANG II were primarily carried out by AT 1 R signaling . Additionally, inhibition of Erk1/2, p38, or Stat3 could also obviously ameliorate the cardiac injury, which cannot completely owe to prevent M1 polarization; as all these inhibitors are not specific for macrophage polarization, more and more data indicated that macrophage polarization was associated with Erk1/2, p38, or Stat3; therefore, our data suggested that to prevent the macrophage polarization, the EAM development could be ameliorated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our data at least indicated that ANG II‐AT 1 R axis played important roles in EAM development and CD11b + Ly6C + cells reprogramming. And our data also were in line with published reports that most actions of ANG II were primarily carried out by AT 1 R signaling . Additionally, inhibition of Erk1/2, p38, or Stat3 could also obviously ameliorate the cardiac injury, which cannot completely owe to prevent M1 polarization; as all these inhibitors are not specific for macrophage polarization, more and more data indicated that macrophage polarization was associated with Erk1/2, p38, or Stat3; therefore, our data suggested that to prevent the macrophage polarization, the EAM development could be ameliorated.…”
Section: Discussionsupporting
confidence: 91%
“…ANG II plays pivotal physiological or pathological roles through ligation with its specific G protein‐coupled receptors, type 1/2 receptor (AT 1 R or AT 2 R). However, most roles were carried out by AT 1 R signaling . Recently, ANG II can serve as a powerful proinflammatory mediator and involve in autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, autoimmune nephritis, and experimental autoimmune encephalomyelitis as well as monocyte and macrophage recruitment .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have also demonstrated that regulation of glomerular hemodynamics by the RAS is impaired in sheep with SFK, suggesting that this may potentially be a system that can be targeted to improve renal outcomes in SFK ( Singh et al, 2011 ). Postnatal adaptive maturation of both blood pressure and glomerular filtration rate (GFR) is associated with the RAS ( Robillard et al, 1983 ; Prevot et al, 2002 ; Vinturache and Smith, 2016 ). In conscious lambs, blood pressure is low at birth and plasma renin activity is elevated but during the first 3 months of post-natal maturation, plasma renin activity decreases as blood pressure increases ( Monument and Smith, 2003 ; Velaphi et al, 2007 ).…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
“…In conscious lambs, blood pressure is low at birth and plasma renin activity is elevated but during the first 3 months of post-natal maturation, plasma renin activity decreases as blood pressure increases ( Monument and Smith, 2003 ; Velaphi et al, 2007 ). Additionally, in the early postnatal period in conscious lambs angiotensin II activation of AT1R regulates GFR and kidney injury associated with glomerular hyperfiltration and hypertrophy may be underpinned by RAS activation ( Babić et al, 2007 ; Vinturache and Smith, 2016 ).…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
“…These receptors selectively and specifically but differently regulate many of the cardiovascular, hemodynamic, renal, neurological, and endothelial functions, cell proliferation and survival, inflammation, and cell-matrix interactions of the RAS. For example, a more important role for AT 2 R than AT 1 R has been shown in fetal development, while AT 1 R is more involved than AT 2 R in mediating Ang II effects for renal function in the postnatal development, maturation, and adaptation. , Ang receptors are classified by their gene sequences, structures of the proteins, ligand-binding affinities, agonist and antagonist efficacies, and signal transduction mechanisms. Pharmacologically, AT 1 R is sensitive to biphenylimidazole, such as the members of the “sartan” family of ARBs, and insensitive to AT 2 R ligands such as tetrahydroimidazopyridines.…”
Section: Modulators Of Ang Receptorsmentioning
confidence: 99%